2006
DOI: 10.1007/s00261-004-0092-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors

Abstract: GISTs can arise anywhere in the gastrointestinal tract and present a great variety of clinical and radiologic features, depending mostly on size and location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 25 publications
2
49
0
6
Order By: Relevance
“…Therefore, when conventional endoscopic and imaging examination fails to locate the lesions in patients with bleeding in a timely manner, emergency DSA may be a useful option. Other characteristics of the patients with small bowel GISTs, such as age, sex and abdominal pain, were similar to previous reports in the literature [2,5,6,13,16] . This study showed that there were some common DSA characteristics in small bowel GISTs.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Therefore, when conventional endoscopic and imaging examination fails to locate the lesions in patients with bleeding in a timely manner, emergency DSA may be a useful option. Other characteristics of the patients with small bowel GISTs, such as age, sex and abdominal pain, were similar to previous reports in the literature [2,5,6,13,16] . This study showed that there were some common DSA characteristics in small bowel GISTs.…”
Section: Discussionsupporting
confidence: 87%
“…Compared with the findings of Fang et al [17] , which showed that draining veins were found only in 27.2% (3/11) of these tumors, we think that the different appearances of the draining veins are mainly based on tumor location, size, and classification. Although CT scans [2,[9][10][11]13,17] also focus on the detection of feeding arteries and tumor blood supply, little attention has been paid to the draining veins of GISTs. In this study, in addition to the clear depiction of feeding arteries, numerous draining veins on tumors also appeared clearly in the early phase of the DSA procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations